2005
DOI: 10.1051/ro:2006001
|View full text |Cite
|
Sign up to set email alerts
|

Online LIB problems: Heuristics for Bin Covering and lower bounds for Bin Packing

Abstract: We consider the NP Hard problems of online Bin Covering and Packing while requiring that larger (or longer, in the one dimensional case) items be placed at the bottom of the bins, below smaller (or shorter) items-we call such a version, the LIB version of problems. Bin sizes can be uniform or variable. We look at computational studies for both the Best Fit and Harmonic Fit algorithms for uniform sized bin covering. The Best Fit heuristic for this version of the problem is introduced here. The approximation rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In the online bin packing problem with LIB (Larger Item in the Bottom) constraints [4,[9][10][11], the subsequence of items which are packed into one bin, a j 1 , a j 2 , . .…”
Section: Alg(i ) Opt(i )mentioning
confidence: 99%
See 1 more Smart Citation
“…In the online bin packing problem with LIB (Larger Item in the Bottom) constraints [4,[9][10][11], the subsequence of items which are packed into one bin, a j 1 , a j 2 , . .…”
Section: Alg(i ) Opt(i )mentioning
confidence: 99%
“…They showed that the competitive ratio of this class of algorithms is at least 2. As for lower bounds, a lower bound of 1.78 on the competitive ratio of any algorithm was claimed in [4]. Unfortunately, there seems to be an error in this proof.…”
Section: Previous Workmentioning
confidence: 99%
“…It is known that its value for classic online bin packing is 5 3 (Zhang 2002;). There are several other packing problems where an offline solution still needs to process the input as a sequence (Finlay and Manyem 2005;Epstein 2009;Dosa et al 2013;Chrobak et al 2011;Balogh et al 2015a, b;Böhm et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that its value for classic online bin packing is 5 3 [30,6]. There are several other packing problems where an offline solution still needs to process the input as a sequence [17,13,12,11,1,2,10].…”
Section: Introductionmentioning
confidence: 99%